2015
DOI: 10.1242/dmm.018952
|View full text |Cite
|
Sign up to set email alerts
|

A novel GAA repeat expansion-based mouse model of Friedreich ataxia

Abstract: Friedreich’s ataxia (FRDA) is an autosomal recessive neurodegenerative disorder caused by a GAA repeat expansion mutation within intron 1 of the FXN gene, resulting in reduced levels of frataxin protein. We have previously reported the generation of human FXN yeast artificial chromosome (YAC) transgenic FRDA mouse models containing 90–190 GAA repeats, but the presence of multiple GAA repeats within these mice is considered suboptimal. We now describe the cellular, molecular and behavioural characterisation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 51 publications
(75 reference statements)
6
68
0
Order By: Relevance
“…5, 47 YG8sR cells carry a 120 GAA repeat in intron 1 of the human FXN transgene resulting in reduced FXN levels to 25% of normal. All experiments were performed on cells before passage 8.…”
Section: Methodsmentioning
confidence: 99%
“…5, 47 YG8sR cells carry a 120 GAA repeat in intron 1 of the human FXN transgene resulting in reduced FXN levels to 25% of normal. All experiments were performed on cells before passage 8.…”
Section: Methodsmentioning
confidence: 99%
“…A successful approach was based on the introduction of a human FXN gene construct in Fxn null mice. Several iterations of this model were suggested based on different GAA expansion lengths . Characterization of the YG8 and YG8sR models, carrying FXN exogenous genes with 90 + 190 or 200 GAA repeats, respectively, showed age‐dependent FRDA symptoms such as ambulatory difficulties, decreased frataxin mRNA levels, abnormal root ganglia, reduced aconitase activity and oxidative stress .…”
Section: Mice Modelsmentioning
confidence: 99%
“…Several iterations of this model were suggested based on different GAA expansion lengths . Characterization of the YG8 and YG8sR models, carrying FXN exogenous genes with 90 + 190 or 200 GAA repeats, respectively, showed age‐dependent FRDA symptoms such as ambulatory difficulties, decreased frataxin mRNA levels, abnormal root ganglia, reduced aconitase activity and oxidative stress . Neurons derived from the YG8 mouse also showed a reduction in Complex I activity, increased oxidative stress in both mitochondria and cytosol, and lipid peroxidation .…”
Section: Mice Modelsmentioning
confidence: 99%
“…The YG8R mouse model has FXN gene targeted alleles and carries two human FXN genes with GAA triplet sequences of 82 and 190 repeats. Previous publications have demonstrated that both C57BL6/ J or wild-type littermates are the correct controls for YG8R mice [26,41]. Thus, the C57BL/6J mouse was used as control in this study.…”
Section: Animals Primary Culture and Cell Linesmentioning
confidence: 99%